PENGARUH PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR SEKOLAH DASAR NEGERI 167 PEKANBARU - Sakilah, Sakilah; Yulis, Ardi; Nursalim, Nursalim; Vebrianto, Rian; Anwar, Abu; Amir, Zubaidah; Sari, Intan Kartika (PD PGMI se Indonesia, 2020)
This study aims to study: the differences between students who take part in spending with a project-based learning model and students who follow learning with conventional models of student learning motivation. This study was a quasi-experimental study with nonequivalent control group design. The population in this study were fifth grade students of Public Elementary School 167 Pekanbaru in 2018/2019. Data collection using tests to determine critical thinking skills and questionnaires to learn learning motivation. Data analysis using t-test and Manova with a significance level of 5%. The results of this study indicate that there are differences between students who take part in spending with a project-based learning model with students who take learning with the conventional model on student learning motivation with the results of data calculations also understand Thitung at 17.412 and P = 0.00.